TINGKAT KONDISI FISIK OLAHRAGA KARATE PADA PERGURUAN YMCA SURABAYA - MEGANTARA BAKHRONI PUTRA, RAHADIAN (Jurnal Kesehatan Olahraga, 2016)
Conditions physical is one of a unity from much a component which is inseparable even by the increasing or maintenance of a physic. One of a famous sport in Indonesia is karate. To achieve an achievement it needs good physical condition in order to maximize a magnificence of Karate. One of a famous Karate school which born great athlete and achieve many achievement is YMCA Surabaya. Those athlete were perform in many competition such as competition among cities, provinces and even among countries. But unfortunately, there is still no physical condition test in YMCA school. The purpose of this study is to know how of the condition physical level in YMCA karate school Surabaya. This study used qualitative-quantitative research which the data came from numbers and words. The final data was in the form of a percentage. The subject of this study were ten male athletes in the age of 13-19 years. The process collect of the data was using test and a measurement are pull up, sit up, multistage fitness test (MFT), zig zug run test, perform word, run 40yrd/37meter, strock stand, standing long jump, sit and reach. While the instrument of this study was stopwatch, measuring tape, sit and reach. The conclusion of this research is the condition physical of YMCA KARATE school of surabaya 2016 can be influence of prestation in individual group and team group. Remembering some of an atlet has good condition physical and less than condition physical to launch a specila training because of can be good condition physical